Tunable Mechanical Filter for Longitudinal Vibrations - S. Asiri (Shock and Vibration)
This paper presents both theoretically and experimentally a new kind of vibration isolator called tunable mechanical filter which consists of four parallel hybrid periodic rods connected between two plates. The rods consist of an assembly of periodic cells, each cell being composed of a short rod and piezoelectric inserts. By actively controlling the piezoelectric elements, it is shown that the periodic rods can efficiently attenuate the propagation of vibration from the upper plate to the lower one within critical frequency bands and consequently minimize the effects of transmission of undesirable vibration and sound radiation. In such a filter, longitudinal waves can propagate from the vibration source in the upper plate to the lower one along the rods only within specific frequency bands called the “Pass Bands” and wave propagation is efficiently attenuated within other frequency bands called the “Stop Bands”. The spectral width of these bands can be tuned according to the nature of the external excitation. The theory governing the operation of this class of vibration isolator is presented and their tunable filtering characteristics are demonstrated experimentally as functions of their design parameters. The concept of this mechanical filter as presented can be employed in many applications to control the wave propagation and the force transmission of longitudinal vibrations both in the spectral and spatial domains in an attempt to stop/attenuate the propagation of undesirable disturbances.